1999
DOI: 10.1097/00000658-199910000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Accuracy of Intraoperative Lymphatic Mapping and Sentinel Lymphadenectomy for Early-Stage Melanoma

Abstract: Lymphatic mapping and sentinel lymphadenectomy can be successfully learned and applied in a standardized fashion with high accuracy by centers worldwide. Successful SN identification rates of 97% can be achieved, and the incidence of nodal metastases approaches that of the organizing center. A multidisciplinary approach (surgery, nuclear medicine, and pathology) and a learning phase of > or =30 consecutive cases per center are sufficient for mastery of LM/SL in cutaneous melanoma. Lymphatic mapping performed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
422
4
21

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 727 publications
(462 citation statements)
references
References 52 publications
15
422
4
21
Order By: Relevance
“…One additional patient presented with metastases in the groin after being mapped in the ipsilateral axillary region. This yields a false-negative sentinel rate of 9.2% and a failure rate of 2.2%, which is in accordance with previous studies (Gershenwald et al, 1999;Morton et al, 1999;Morton et al, 2003;Vuylsteke et al, 2003). As previously shown by Gershenwald, detection failure of positive SLNs most commonly occurs because conventional histologic evaluation is unable to identify occult metastatic disease (Gershenwald et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…One additional patient presented with metastases in the groin after being mapped in the ipsilateral axillary region. This yields a false-negative sentinel rate of 9.2% and a failure rate of 2.2%, which is in accordance with previous studies (Gershenwald et al, 1999;Morton et al, 1999;Morton et al, 2003;Vuylsteke et al, 2003). As previously shown by Gershenwald, detection failure of positive SLNs most commonly occurs because conventional histologic evaluation is unable to identify occult metastatic disease (Gershenwald et al, 1998).…”
Section: Discussionsupporting
confidence: 89%
“…3,8,[20][21][22][23][24][25] Technical failures may occur as a result of errors in lymphatic mapping and sentinel lymphadenectomy or because of a deficiency in the process of histopathologic evaluation. With long-term follow-up of patients with negative sentinel nodes there is a small but definite incidence of recurrence in the mapped and sampled nodal basin.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Furthermore, the presence or absence of metastases in the sentinel node is the most important prognostic factor for melanoma patients. 9 For a sentinel node to provide accurate prognostic information, it is essential that 'true' sentinel nodes are removed and examined thoroughly.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that using a combination of the two methods improves results. 11,12 The idea is that either technique will identify the first echelon lymph node(s) draining the tumor site. 13 Many centers also use preoperative mapping with the addition of single photon emission CT (SPECT) to determine the location of the lymph node prior to surgery.…”
Section: Introductionmentioning
confidence: 99%